(untitled) (Faridpur Medical College Journal, 2012)
Chronic Kidney Disease (CKD) presents with an array of cutaneous manifestations. Newer changes are being described since the advent of haemodialysis, which prolongs the life expectancy, giving time for these changes to manifest. This cross sectional study was performed in 100 cases of CKD admitted in nephrology department of Dhaka Medical College Hospital (DMCH) and Bangabandhu Sheikh Mujib Medical University (BSMMU) from April 2008 to August 2008 to evaluate the prevalence of dermatologic problems. Among them most belong to 2nd to 5th decade, 68 are male and rests are female. Glomerulonephritis (44%), Diabetes mellitus (22%), Obstructive uropathy (13%) and Hypertensive nephropathy (12%) are found common causes of CKD. Among these patients 38% patients were treated with conservative treatment, 31% with intermittent peritoneal dialysis (IPD), 19% with haemodialysis and 12% with some form of immunosuppressive therapy. Total 88% of study population had some form of skin disorder; pallor was the most common (82%), while xerosis (61%), pruritus (53%), pigmentation (37%) and bacterial infection (37%) were other common problems. Purpura and fungal infection was 29% and 27% respectively. Viral infection (9%), dermatitis (4%), gynaecomastia (1%), kyrle’s disease (3%) are relatively less common findings. Lindsay’s nail was seen in 23% of patients and was more prevalent in glomerulonephritis and diabetic patients with prevalence of 13% and 9% respectively. Other nail changes included koilonychia (4%), subungual hyperkeratosis (1%), splinter hemorrhages (3%) onychomycosis (8%) and Beau’s lines (1%). So, CKD is associated with a complex array of cutaneous manifestations caused either by the disease or by treatment. DOI: http://dx.doi.org/10.3329/fmcj.v7i1.10296 Faridpur Med. Coll. J. 2012;7(1): 33-36